Identity politics and economic development in Sabah, Malaysia during PBS era, 1985-1994 - Madiyem Layapan (2023)
This thesis investigates the significance of identity politics in the undeveloped economy of Sabah during the reign of Parti Bersatu Sabah (PBS) (1985-1994). Scholars frequently argue that any state's economic development is heavily influenced by government policies, external parties such as international socioeconomic movement and competition among local and international business communities, and citizens' socioeconomic activities. This resulted in an incorrect assessment of the importance of other factors in economic development, particularly identity politics. For this reason, the thesis contends that a state's economic development frequently has a strong relationship with identity political activities among its citizens, particularly the politicians who are always interested in gaining or retaining political power. The thesis also contends that the connection between identity politics and economic development is mediated by federal-state relations and in-group favouritism among political leaders. In order to determine the significance of identity politics in the undeveloped economy of Sabah during the PBS era, the thesis also investigates the mediating role of prolonged federal-state relations and in-group favouritism among political leaders in this context. Through the application of ethnohistorical investigation using a mixed-method design, this thesis demonstrates that political identity played a significant role in the underdeveloped economy of Sabah, Malaysia during the reign of PBS. It is also appeared that both prolonged federal-state relations and in-group favouritism among political leaders played a significant mediating role in the relationship between identity politics and the underdeveloped economy of Sabah, Malaysia during the PBS era. The case of Sabah clearly demonstrates how identity politics affects the economic development of a resource-rich state in a modern democratic federation country, making the country vulnerable to ethnoreligious conflict. As a result, from a policy standpoint, this thesis implies the importance of ending identity political practices to prevent the country from decaying. Most importantly, such a move is required not only to prevent politicians with a lack of integrity from dominating politics, but also to ensure the provision of more universal benefits to citizens and the prevention of full-fledged conflict within an ethnically and religiously diverse population.